Male cephalic labial gland secretions of two bumblebee species of the subgenus Cullumanobombus (Hymenoptera: Apidae: Bombus latreille) and their distribution in central Europe - Hovorka, Oldrich; Valterová, Irena; Rasmont, Pierre; Terzo, Michaël (Chemistry & biodiversity, 2006)
The cephalic labial gland secretion of Bombus semenoviellus males was analyzed, and its chemical composition is reported for the first time. The secretion functions as sex or marking pheromone. Eighty compounds were identified in the secretion, the main one being all-trans-geranylgeranyl acetate (48%). The same compound was shown to form 87% of the labial gland secretion of B. cullumanus males. Both species are closely related and belong to the subgenus Cullumanobombus.
Keywords: Hymenoptera; pachové žlázy; Sex Attractants; Phylogeny; Evropa; Europe; Male; Animals; Scent Glands; sexuální lákadla; mužské pohlaví; zvířata; fylogeneze